EFEKTIVITAS INOKULUM FUNGI MIKORIZA ARBUSKULA LOKAL TERHADAP PERTUMBUHAN TANAMAN KACANG HIJAU (Vigna radiata L.) - Angri Durisa Selan; Abdonia W. Finmeta; Nur Aini Bunyani; Deglory Tunmuni (Adisam Publisher, 2025)
Arbuscular Mycorrhizal Fungi (AMF) Are types of fungi that inhabit the soil and always collaborate with higher plants, providing mutual benefits to each other. This association is formed because AMF consistently inhabits the root system of the host plant and provides mutual benefits. In Latin, the term “arbuscula” comes from the word “arbuscula”, describing a tree-like structure that grows inside the root cortex cells of the host plant (sukarno , 2023). This study aims to evaluate the effectiveness of local arbuscular mycorrhizal fungi (AMF) inoculum in increasing the growth of mung bean plants (Vigna radiata). The study used a completely randomized experimental design (CRD) with treatments repeated 4 times so that 16 experimental units were obtained M0: Control(without AMF inoculum), M1: AMF inoculum from Nano, M2: AMF inoculum from HTC Bu’at , M3: AMF inoculum from sisimeni sanam. In this study, 4 treatments were carried out and repeated 4 times so that there were 16 experimental units. The results showed that the provision of local AMF significantly increased plant growth compared to the control. This shows that local AMF has the potential to be used as a natural biofertilizer to increase green bean productivity sustainably.